2020
DOI: 10.1126/scitranslmed.abb8969
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic reprogramming of donor T cells enhances graft-versus-leukemia effects in mice and humans

Abstract: Acute myeloid leukemia (AML) relapse after allogeneic hematopoietic cell transplantation (allo-HCT) has a dismal prognosis. We found that T cells of patients relapsing with AML after allo-HCT exhibited reduced glycolysis and interferon-γ production. Functional studies in multiple mouse models of leukemia showed that leukemia-derived lactic acid (LA) interfered with T cell glycolysis and proliferation. Mechanistically, LA reduced intracellular pH in T cells, led to lower transcription of glycolysis-related enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(75 citation statements)
references
References 42 publications
2
65
1
Order By: Relevance
“…Recent findings in immune cell metabolic reprogramming indicated the possibilities of clinical metabolic interventions for cancer treatment ( 12 , 146 ). Metabolic intervention by sodium bicarbonate helps neutralize the lactate acidity in AML, leading to improved efficacy of CD8+T cell immunotherapy ( 147 ). Pearce group showed that transient glucose restriction (TGR) in CD8+effector T cell before adoptive transfer metabolically condition effector T cell functions and enhance tumor clearance in mice ( 148 ).…”
Section: A New Frontier Of Conditioning Metabolism To Enhance Immune Effector Cell Functions In Immunotherapiesmentioning
confidence: 99%
“…Recent findings in immune cell metabolic reprogramming indicated the possibilities of clinical metabolic interventions for cancer treatment ( 12 , 146 ). Metabolic intervention by sodium bicarbonate helps neutralize the lactate acidity in AML, leading to improved efficacy of CD8+T cell immunotherapy ( 147 ). Pearce group showed that transient glucose restriction (TGR) in CD8+effector T cell before adoptive transfer metabolically condition effector T cell functions and enhance tumor clearance in mice ( 148 ).…”
Section: A New Frontier Of Conditioning Metabolism To Enhance Immune Effector Cell Functions In Immunotherapiesmentioning
confidence: 99%
“… 43 The importance of the glycolytic activity of T-cells to enhance GvL immunity was recently demonstrated. 47 T-cells from patients relapsing after allo-HCT showed reduced glycolysis that was mechanistically linked to increased lactic acid secreted by leukemia cells leading to a reduction of the intracellular pH in T-cells. Metabolic reprogramming of donor T-cells enhanced GvL activity and prolonged the survival of leukemia-bearing mice.…”
Section: Metabolic Reprogramming Of T-cellsmentioning
confidence: 99%
“…Multiple approaches are under investigation to improve the after-transplantation overall survival [ 109 ] in elderly patients. They range from the combinations with different chemotherapies [ 110 ] and radiotherapies to enhance T cells’ metabolic activity restoring the GVL [ 111 ].…”
Section: Adoptive Cell Transfermentioning
confidence: 99%